Friction and wear behaviors of carbon and aramid fibers reinforced polyimide composites in simulated space environment. (December 2015) - Lv, Mei; Zheng, Fei; Wang, Qihua; Wang, Tingmei; Liang, Yongmin
Abstract: The friction and wear behaviors of carbon and aramid fibers reinforced polyimide composites have been investigated in simulated space irradiation environment and start–stop friction process. The experiment results showed that the introduction of fibers decreased the friction coefficient and improved the wear-resistance of polyimide matrix after atomic oxygen and ultraviolet irradiations especially for the carbon fibers. A start–stop friction process aggravated the wear of various composite materials against the counterpart ball. Carbon fibers reinforced polyimide displayed excellent tribological property in irradiation environment and start–stop friction condition, which was expected to become a kind of potential tribological material for the application of spacecraft. Highlights: The introduction of fibers decreased the friction coefficient and wear rate of polyimide. AO/UV irradiations could damage the molecular chain of polyimide. The start–stop friction process aggravated the wear of materials. Carbon fibers/polyimide composites displayed excellent tribological property in irradiation environment.